ANALYSIS OF ANESTHESIA COMPLIANCE FACTORS IN THE ANESTHESIA DOCUMENTATION PROCESS - Safruddin Marwan; Vita Purnamasari; Ratih Kusuma Dewi (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
Background: Anesthesia documentation is an important part of nurse anesthetist to ensure patient safety and compliance with health service standards. However, the level of compliance of nurse anesthetist in documentation still varies. Non-compliance in documentation can lead to incomplete information, potentially affecting the quality of patient care and the safety of anesthesia procedures. Objective: This study aims to analyze the factors that influence the compliance of nurse anesthetist in the process of documenting anesthesia at dr. Soedirman Hospital of Kebumen. Methods: This study applied a descriptive qualitative approach with a single case study design using thematic analysis method. The participants of the study were nurse anesthetist working at dr. Soedirman Hospital of Kebumen as many as 3 participants selected using purposive sampling techniques. Data collection was carried out through semi-structured interviews and observations. Results: The results of the study identified three main themes that influenced the compliance of nurse anesthetist in documenting anesthesia, namely: theme I the process and obstacles in documentation, theme II internal factors that influence compliance such as knowledge, attitudes, and motivation, theme III external support and workload such as supporting facilities and evaluation from supervisors. Conclusion: Nurse anesthetist’ compliance in anesthesia documentation is influenced by internal and external factors.